PERAN, TANTANGAN, DAN REORIENTASI PENDIDIKAN AGAMA ISLAM DI ERA SOCIETY 5.0 - Ade Zaenul Mutaqin; Ajang Ramdani; Ardiansyah Kurniawan (INTEGRATIF |Jurnal Magister Pendidikan Agama Islam, 2025)
This article discusses the role, challenges, and reorientation of Islamic religious education in the context of Society 5.0, where technology and digital social interactions have become integral parts of everyday life. In this era, Islamic religious education faces various challenges, including the lack of technology integration in learning, declining interest among the younger generation, and a gap between theory and practice. This study aims to identify these challenges and propose a necessary reorientation to increase the relevance of Islamic religious education. Through a systematic literature review, this article suggests the implementation of technology-based learning methods, the development of curricula responsive to social change, and ongoing training for educators. The results show that with appropriate reorientation, Islamic religious education can adapt well to the era of Society 5.0 and continue to contribute to the formation of students' character and morality. This article is expected to provide insights and recommendations for policymakers and education practitioners in facing the challenges of the digital era.